Adipose tissue expression of adipose (WDTC1) gene is associated with lower fat mass and enhanced insulin sensitivity in humans. (11th June 2013) - Galgani, Jose E.; Kelley, David E.; Albu, Jeanine B.; Krakoff, Jonathan; Smith, Steven R.; Bray, George A.; Ravussin, Eric; ,
Abstract : The overexpression of the adipose gene ( adp /WDTC1) in mice inhibits lipid accumulation and improves the metabolic profile. Objective: Subcutaneous fat adp expression in humans and its relation to metabolic parameters was evaluated. Design and Methods: Abdominal subcutaneous fat adp expression, insulin sensitivity (clamp), and respiratory quotient (RQ; indirect calorimetry) were assessed in: 36 obese and 56 BMI‐, race‐, and sex‐matched type 2 diabetic volunteers (Look AHEAD Adipose Ancillary Study); 37 nondiabetic Pima Indians including obese ( n = 18) and nonobese ( n = 19) subjects and; 62 nonobese nondiabetic subjects at the Pennington Center in the ADAPT study. Results: In the Look AHEAD Study, adp expression normalized for cyclophilin B was higher in males versus females (1.27 ± 0.06 vs. 1.11 ± 0.04; P < 0.01) but not after controlling for body fat. Adp expression was not influenced by the presence of diabetes but was related to body fat ( r = −0.23; P = 0.03), insulin sensitivity ( r = 0.23; P = 0.03) and fasting/insulin‐stimulated RQ ( r = 0.31 and 0.33; P < 0.01). In Pima Indians, adp expression was also higher in males versus females (1.00 ± 0.05 vs. 0.77 ± 0.05; P = 0.02) and higher in nonobese versus obese (1.02 ± 0.05 vs. 0.80 ± 0.06; P = 0.03). In the ADAPT study, there was no difference in adp expression between males and females. Conclusion: Consistent with animal studies, our results suggest that high adp expression in human adipose tissue is associated with lower adiposity and enhanced glucose utilization.